End user evalution of descriptive metadata elements and user interface design of digital art image database in selected Malaysian art institutions - Safura Idris (Kulliyyah of Information Communication & Technology, International Islamic University Malaysia, 2010)
Advances in computer and multimedia technologies have resulted in the increased size of digital images. As a result, it is necessary to design automated multimedia retrieval systems that can operate on a large scale basis. Library and information institutions around the world are also taking advantage of digital technologies as evidenced from the increased number of digitisation projects. Cultural heritage information institutions in Malaysia have also digitised their collections, resulting into a number of digital art repositories being accessible on the World Wide Web. The study identified the current state of digitisation of art collection in selected Malaysian art institutions in terms of their type of collections and the size of collections. This study aimed to investigate the creation of metadata for digital art images, which emphasized on the description of metadata applied in the selected Malaysian art institutions. The research further investigated the type and level of collection being displayed as well as on how the image was searched and browsed. The study further focused on end-user perceptions, which specified on the usefulness, suitability, and importance of descriptive metadata of digital art repositories in the selected Malaysian art institutions. In addition, the study investigates end user's perception on the interface design features of digital art databases in the selected Malaysian art institutions. The findings of this research were useful as a guideline for the development of descriptive metadata of digital art images and effective interface design for end user to search and browse for digital art images.